Eaux, risques majeurs et patrimoine culturel : des directives européennes aux stratégies territoriales, état des lieux de la mise en œuvre en France - Virginie Serna (Développement Durable et Territoires)
The implementation of the Water Framework Directive (WFD or Directive 2000/60/EC of the European Parliament and of the Council of 23 October 2000 establishing a framework for Community action in the field of water policy) and the Floods Directive FD) in the country represents a major challenge for cultural heritage. It has resulted in the reevaluation, reconstruction, or destruction of heritage linked to water management in all its forms (river management, hydraulic engineering ...) and in the management of risks caused by water (dikes, embankments, coastal maintenance works, drainage ditches ... ). They forced those involved in heritage management to consider the heritage resources associated with water ; to recognise them and to identify actions in order to heighten awareness and secure their protection. These heritage enquiries in regiontake different forms (inventories, university programs, inter-ministerial working groups ...) and they must be interlinked in order to show that natural and cultural heritage ressources inseparable.